PEMBERDAYAAN EKONOMI MELALUI WAKAF (UIN Sunan Kudus, 2017)
Waqf has an economic value where waqf is a potential source of funds for people who need to be developed, utilized, and managed professionally to obtain optimal results. In order to mobilize the potential of waqf, a partnership should be made of the endowments established by the community and the representative bodies established by the Government. The purpose of waqf regulation from the economic aspect is to improve the welfare of Muslims and the Indonesian nation. In addition, to accommodate the growing potential of waqf that is increasingly diverse in line with modern economy such as cash waqf. There are several obstacles that impede the implementation of cash waqf in accordance with the provisions of Law no. 41 of 2004, among which are; first, the Indonesian Waqf Board (BWI) does not have the operational power in the area of sufficient money waqf. Second, the principle used in the implementation of waqf money is too rigid, ie the bank is purely as a bank. Thus, the Wakifwho performs cash waqf is treated the same with other customers.